Аналіз методів розподілу ресурсів на основі сегментації 6G мережі - Скомаха, М. О; Єременко, О. С. (ХНУРЕ, 2024)
This work reviews and analyzes segmentation methods that can be used for resource allocation in 6G networks. The emphasis is placed on the use of slicing and deep slicing technologies, as well as on the advantages of such methods for maintaining the optimal level of QoS. The challenges of implementing this technology are also discussed, including integration, interaction with artificial intelligence, resource management, and standardization to achieve maximum efficiency in the 6G environment.
Keywords: розподіл ресурсів; сегментація; 6G